THE EFFECT OF ADMINISTERING THE ANTIBIOTIC CYPROTYLOGRIN ON THE PRODUCTION OF LAYING CHICKENS IN THE LAYER PHASE DURING THE RECOVERY PERIOD AT CV BERKAT KARYA GEMILANG KARANGANYAR - Defa Fernando; Kukuh Hari Iswanto; Ludfia Windyasmara (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
This study aimed to analyze the effect of administering Cyprotylogrin Antibiotic on the performance of laying hens during the recovery period in the layer phase at CV Berkat Karya Gemilang. The study used a quasi-experimental method with two treatment groups, namely group A (Cyprotylogrin Antibiotic + vitamins) and group B (vitamins only), each consisting of 1,300 hens. Observations were conducted for 14 days on egg production (trays), egg weight (kg), and feed intake. Data were analyzed using the Independent Samples T-Test.The results showed that the treatment group had a higher average egg production (35.36 trays) compared to the control group (33.65 trays), with a significant difference (P < 0.01). The average egg weight was also higher in the treatment group (67.57 kg) compared to the control group (63.34 kg), with a highly significant difference (P < 0.01). For the feed intake variable, there was a significant difference (P = 0.05). It can be concluded that the administration of Cyprotylogrin Antibiotic had a significant effect on improving the production performance of laying hens during the recovery period in the layer phase